Development of an intelligent immune agent management system for facilitating e- diagnosis in manufacturing environment - Rahul Walia (2008)
The objective of this dissertation is to design and implement an agent framework for the support of electronic prognostics of machinery. It deals with dual communication i.e. one originating from the sensors that is relayed to various reception centers and the other originating from the intelligent prognostics engine fed back to the control mechanism of the machinery. More specifically this dissertation concentrates on the development of peer agent communication, communication ontologies, agent behaviors based on messaging performatives, integration issues and graphical user interfaces for diverse agents and human interfaces. It also evolves the conceptual agent framework for the deployment in a manufacturing environment. The conceptual design and prototype model establishes the applicability of agent framework in diagnostics as well as prognostics. The framework is developed using the Java Agent Development Framework (JADE).